Application of a mild hydrothermal method to the synthesis of mixed transition-metal(ii)/uranium(iv) fluorides. Issue 2 (9th January 2017) - Felder, Justin; Yeon, Jeongho; Smith, Mark; zur Loye, Hans-Conrad
Abstract : The synthesis and properties of two families of mixed metal U(iv )/M(ii ) fluorides via a mild hydrothermal method. Abstract : Single crystals of five transition metal uranium fluorides were obtained via the use of a mild hydrothermal route. Uranyl acetate was used as both the uranium source and the reducing agent for an in situ reduction of U(vi ) to U(iv ). The synthesized materials are present as both two- and three-dimensional structures and contain uranium in 9-fold coordination environments. Magnetic susceptibility measurements indicate that the reported materials remain paramagnetic down to 2 K, with no evidence for the existence of long-range magnetic ordering. Thermogravimetric analysis studies of the reported materials are also presented.